Sifat Antioksidatif Ekstrak Buah Duwet (Syzygium cumini) - Lydia Ninan Lestario; Pudji Hastuti; Sri Raharjo; Tranggono Tranggono (agriTECH, 2005)
A research on Java plum (Syzygium cumini) fruit as source of natural antioxidant has been done with special emphasis on the role of anthocyanins. The aims of this research were : to determine the extraction condition which include types of solvents, length of time, and temperature of extractions. The solvents combination consisted of : methanol-HC1 1%; acetone; acetone-water (7:3); and water, which were applied for 4, 8, 12 hours extractions at room (27-29°C) and cool room (4°C) temperatures. The results showed that methanol-HCI I% gave highest extract of anthocyanins and polyphenols and antioxidant activity as compared to acetone, acetone-water (7:3), and water. Higher antioxidant activity and anthocyanin content were resulted from extraction in 4°C compared to room temperature; whereas higher polyphenol content were obtained from extraction at room temperature compared to cool room temperature. The length of extraction time. did not give significant differences in antioxidant activity, anthocyanin and polyphenol content. With regard to methanol-HC1 1% extract, there was a sienificant correlation between anthocyanin level and antioxidant activity (Y= 12,20 X + 84,40 ; r=0,900), and nonsignificant correlation between polyphenol content and antioxidant activity (Y= -0,92 X + 144 ; r=-0,805) (r table = 0,811); These facts indicated that the anthocyanin had a high antioxidant activity.Key words: Syzygium cumini, antioxidant activity, anthocyanin, polyphenol.